Developing Creative Artwork Through The Use Of Social Media: A Case Study Of Arts Students In Penang - Balraj Baboo, Shanthi; Lim , Jing Yi (2015)
The use of social media as part of learning and information searching tool is increasing significantly among the students of higher learning institutions. This paper explores how the creative art students engage with the social media for creative purposes and presents selected findings of wider study on creative development in the digital era. Using a sample of 300 students from public and private universities and colleges, the study aims to look at two specific themes: (i) The ways students use social media as a platform for generating information and discussion; (ii) the hopes and fears of creative students in facilitating their ideas and works in this platform. Using a mixed methodology, the study uses questionnaires to unveil the students' knowledge and practices in developing creative artwork. Interviews are also conducted to get rich insights of some of the joy and triumphs as well as challenges and fears they confront when using social media for developing creative artwork. The findings reveal that social media creates a new platform for these students to conduct their discussion; it acts as one of the information resources for developing creative projects at both local and global levels. Further, social media provides a space for interaction in getting comments and feedback especially from people with different backgrounds for a better quality artwork. While social media is also one the new approaches for creative art students to promote and exhibit their artwork to a wider group of audience, they are also fearful of theft of creative ideas and issues of copyright and patent of their ideas. By way of conclusion, this paper discusses some of the opportunities and risks in using social media for students' creative artwork.